Women’s Stereotypes in Indonesian and Korean Pocari Sweat 2018 Ads - Fitriyah, Aidatul; Sindangsari, Laura Putri; Aydinovich, Gashimov Elchin (Lingua : Journal of Linguistics and Language, 2024)
This study analyzes the visualization of gender stereotypes in Indonesian and Korean Pocari Sweat advertisements 2018 using Roland Barthes' semiotic theory. The research aims to compare and interpret how gender roles are portrayed in these advertisements, reflecting the cultural contexts of Indonesia and Korea. A qualitative method was applied, utilizing Barthes' semiotic analysis to examine the primary data—images extracted from the advertisements. Secondary data, including literature reviews and relevant studies, provided additional context. The data collection process involved selecting advertisements, segmenting visual elements, and analyzing their meanings based on denotation and connotation. Findings indicate that Indonesian Pocari Sweat advertisements reinforce patriarchal values by depicting women in supportive roles, often serving men. In contrast, Korean advertisements promote a feminist perspective, showcasing women engaging in physically demanding activities, challenging traditional gender norms. These differences highlight the cultural disparities in gender perceptions between the two countries. The study concludes that advertising serves as a medium that reflects and perpetuates societal gender norms. Indonesian advertisements maintain traditional gender roles, while Korean advertisements align with progressive feminist movements. This research underscores the role of media in shaping public perceptions of gender and contributes to discussions on gender representation in advertising.